Prototype Alat Pengaman Lemari Penyimpanan Barang Menggunakan ESP32 Cam Berbasis IOT di Yayasan Panti Asuhan Ar Rohmah Blitar - Nadiyan Ishom Abu Sahal, Ahmad; Wulansari, Zunita; Dwi Romadhona, Rizki (Green Publisher Indonesia, 2024)
Security is the most important thing in our lives that can provide comfort and a sense of security for something we own, whether it is in the form of valuable items or documents that we store and protect from irresponsible individuals or other parties who have bad intentions in this research. aims to design, build and test security equipment for storage cupboards using IoT-based Esp32 cam at the Ar Rohmah Blitar orphanage foundation to improve security at the Orphanage Foundation in the goods storage cupboard sector. This research was conducted at the Ar Rohmah Blitar Orphanage Foundation in the Sananwetan area of Blitar City, starting from December 2023 to July 2024. In this research, researchers used the Research and Development (RnD) research method. This research produces an IoT-based foundation cupboard security device. The design of the tool begins with designing a series of tools, then continues with creating a Telegram Bot as a user interface and a program for the Esp32 Cam microcontroller as a tool for locking and securing cabinets. Then it continues with the tool testing stage carried out by researchers, experts and users. From testing carried out by researchers, an accuracy value of 81% was obtained in the